PEMBUATAN PROTOTIPE LAMPU OTOMATIS UNTUK PENGHEMATAN ENERGI BERBASIS ARDUINO UNO DI DEPARTEMEN FISIKA FMIPA IPB - Nida Nabilah; Hannif Izzatul Islam; Dendy Handy Saputra; Gagat Mughni Pradipta; Sofyan Said; Ade Kurniawan; Heriyanto Syafutra (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Prototipe automation lamp for saving energy has been successfully creating based on arduino uno. It is assited by PIR (passive infrared) sensor and RTC (real time clock) module. For proving sensitivity PIR, performed an experiment use a distance that is 0 meter, 0.5 meter, 1 meter, 1.5 meter, 2 meter, 2.5 meter, and 3 meter and an angle of 0 degree, 30 degree, 45 degree, and 60 degree with the source motion is the human movement. In this experiment is showed that in the distance of 2.5 meter and angle 60 degree PIR sensor can’t reach the source motion. Real time clock is used to set the active sensor PIR before detected source motion. It make more effective so there is no reduce of energy, because time of consuming lamp which active during 1x24 hours. Keywords: Arduino Uno, Automation Lamp, PIR Sensor, RTC, Saving Energy